2023
DOI: 10.3389/fncel.2023.1191629
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunctions induce PANoptosis and ferroptosis in cerebral ischemia/reperfusion injury: from pathology to therapeutic potential

Abstract: Ischemic stroke (IS) accounts for more than 80% of the total stroke, which represents the leading cause of mortality and disability worldwide. Cerebral ischemia/reperfusion injury (CI/RI) is a cascade of pathophysiological events following the restoration of blood flow and reoxygenation, which not only directly damages brain tissue, but also enhances a series of pathological signaling cascades, contributing to inflammation, further aggravate the damage of brain tissue. Paradoxically, there are still no effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 253 publications
(293 reference statements)
0
8
0
Order By: Relevance
“…Recent trends in PANoptosis have led to a proliferation of studies of altered genes in tumors 10 12 . However, within vascular disease, comparably little attention has been given to possible roles for PANoptosis 13 , 14 . Previous studies have suggested that apoptosis and smooth muscle cell (SMC) proliferation may play an important role in arterial remodeling in MMD 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent trends in PANoptosis have led to a proliferation of studies of altered genes in tumors 10 12 . However, within vascular disease, comparably little attention has been given to possible roles for PANoptosis 13 , 14 . Previous studies have suggested that apoptosis and smooth muscle cell (SMC) proliferation may play an important role in arterial remodeling in MMD 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is an urgent global need to explore the comprehensive pathogenic mechanisms and effective diagnostic and therapeutic methods for ischemic stroke. Increasing evidence suggests that ischemia-reperfusion injury is an important link in the pathogenesis of ischemic stroke, and in this process, the regulation of cellular physiological processes such as mitophagy and ferroptosis becomes particularly crucial ( Liu et al, 2013 ; Zhang et al, 2022a ; She et al, 2023 ). Ischemia-reperfusion injury in cerebral strokeresults from cellular damage due to insufficient cerebral blood flow, exacerbated by oxidative stress and inflammatory reactions during reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…This in ammatory response exacerbates brain tissue damage and potentially hinders neural functional recovery. Therefore, a thorough understanding of the pathophysiological mechanisms of ischemic brain injury, particularly the role of immune-in ammatory responses, is crucial for developing novel therapeutic strategies (10,11,12).…”
Section: Introductionmentioning
confidence: 99%